Cytokines as potential biomarkers for the diagnosis of Mycobacterium bovis infection in Mediterranean buffaloes (Bubalus bubalis) - Franzoni, Giulia; Signorelli, Federica; Mazzone, Piera; Donniacuo, Anna; De Matteis, Giovanna; Grandoni, Francesco; Schiavo, Lorena; Zinellu, Susanna; Dei Giudici, Silvia; Bezos, Javier; De Carlo, Esterina; Galiero, Giorgio; et al. (Frontiers in Veterinary Science, 2024)
Mycobacterium bovis (M. bovis) is the primary agent of bovine tuberculosis (TB) in Mediterranean buffalo, which has a negative economic impact on buffalo herds. Improving TB diagnostic performance in this species represents a key step to eradicate efficiently this disease. We have recently shown the utility of the IFN-γ assay in the diagnosis of M. bovis infection in Mediterranean buffaloes (Bubalus bubalis), but other cytokines might be useful immunological biomarkers of this infection. We therefore investigated the utility of key immune cytokines as diagnostic biomarkers of M. bovis infection in this species. Thirty-six Italian Mediterranean buffaloes were used in this study: healthy animals (N = 11), infected (IFN-γ test positive, no post-mortem lesions, no M. bovis detection; N = 14), and affected (IFN-γ test positive, visible post-mortem lesions; N = 11). Heparin blood samples were stimulated with bovine purified protein derivative (PPD-B), alongside controls, and 18–24 h later plasma were collected. Levels of 14 key cytokines were measured: IFN-γ, IL-17, IL-4, IL-10, TNF, IL-1α, IL-1β, IL-6, IP-10, MIP-1α, MIP-1β, MCP-1, IL-36Ra, and VEGF-A. We observed that both infected and affected animals released higher levels of IFN-γ, IL-17, IL-10, TNF, IL-1α, IL-6, MIP-1β, in response to PPD-B compared to healthy subjects. Mycobacterium bovis infected animals released also higher levels of IL-1β and IP-10 in response to PPD-B compared to healthy subjects, whereas only tendencies were detected in affected animals. Affected animals only released MIP-1α in response to PPD-B compared to healthy subjects and in this group higher values of PPD-B specific TNF was also observed. Finally, canonical discriminant analysis (CDA) was used to generate predictive cytokine profiles by groups. Our data suggest that IL-10, TNF, IL-1α, IL-6, MIP-1β could be useful biomarkers of TB in Mediterranean Buffalo and can improve the TB diagnostic performance in this specie.